Pengaruh Motivasi Kerja terhadap Kinerja Karyawan pada Kantor Permodalan Nasional Madani (PNM) Cabang Jambi - Yogi Sardi (Science of Management and Students Research Journal (SMS), 2022)
This study aims to obtain an overview of work motivation and employee performance at the Jambi branch of the National Civil Capital Office (PNM). Data was collected by distributing questionnaires to 81 employees. The aspects studied are 5 dimensions of work motivation, namely physiological needs, security needs, social needs, recognition needs, and self-actuality needs. As well as the performance aspects studied include work results, job knowledge, initiative, mental dexterity, attitude, time discipline and absenteeism.Testing the data using statistical analysis such as validation and reliability tests, simple linear regression analysis, hypothesis testing t test and coefficient of determination test from the results of the analysis with SPSS version 22 program, it can be seen that the regression equation formed by linear regression is Y=25,498+0,449X. The equation shows that the employee's performance is 0 then work motivation will increase by 0.449. From the results of the analysis, it is known that the results of R square indicate that there is an influence of work motivation of 22.9% on employee performance, thus in research work motivation that affects the average performance of the total influence of work motivation on employee performance as a whole is 22.9 and the remaining 77.1 is influenced by other factors not included in this study. Overall, from the 5 dimensions of the work motivation variable, it has an average score of 351.64 which is categorized as good. Where obtained a description of the work motivation used by the employees of the Jambi branch of the National Capital Office (PNM) which is good for motivating work on the basis of consideration and good for work motivation. Motivation has a positive and significant effect on the performance of the employees of the Jambi branch of the National Civil Capital Office (PNM).